Literatur Review Efektivitas Penggunaan Streptokinase Pada Pasien Infark Miokard Akut - Musdalifa; Wisudawan; Purwati Pole Rio (2026)
Acute myocardial infarction (AMI) is a leading cause of death from ischemic heart disease, characterized by sudden blockage of the coronary arteries. One of the main therapies to treat this blockage is the administration of streptokinase, a thrombolytic agent that functions to dissolve blood clots. This paper aims to assess the effectiveness of streptokinase use in patients with AMI through a literature review of various international and national clinical studies. The method used is a literature review with descriptive analysis of relevant research results. The study results indicate that early administration of streptokinase can reduce mortality and improve patient prognosis, despite the risk of allergic reactions and lower efficacy compared to newer generation thrombolytics. However, due to its widespread availability and lower cost, streptokinase remains the primary treatment of choice in many developing countries.